The peacemaker : Ronald Reagan, the Cold War, and the world on the brink - Inboden, William, 1972- (Dutton, an imprint of Penguin Random House LLC, 2022)
"An in-depth and masterful account of how Ronald Reagan's foreign policy 'team of rivals' ended the Cold War and laid the foundation for the twenty-first century. Today, the ending of the Cold War seems a foregone conclusion. But in the early 1980s, U.S. intelligence predicted the Soviet Union would last another century. Ronald Reagan entered the White House with no certainty of what would happen next, only an overriding faith in American democracy and an abiding belief that the communist system--and the threat of nuclear war--must be brought to an end. The Peacemaker is the story of the eight years of Reagan's presidency, as he and his foreign policy team managed, in real time, multiple crises around the globe. From the emergence of global terrorism, wars in the Middle East, the rise of Japan and the awakening of China, to proxy conflicts in Latin America, Africa, and Asia, Reagan's team oversaw the worldwide expansion of democracy, globalization, free trade, and the information revolution. Yet no issue was greater than the Cold War standoff with the Soviet Union. As president, Reagan cast aside the four-decades-old policy of containment and challenged the Soviets in an arms race that pushed them towards economic and political collapse, all while extending an olive branch of diplomacy. Reagan's revolving team included Secretaries of State Al Haig and George Schultz; Secretaries of Defense Caspar Weinberger and Frank Carlucci; National Security Advisors Bill Clark, John Poindexter and Bud McFarlane; Chief of Staff James Baker; CIA Director Bill Casey; and Jeane Kirkpatrick, Reagan's United Nations ambassador who fell out with the president over the Falkland War. Talented and devoted to their cause, at times their inner rivalries and backstabbing led to missteps and crises. But over the course of the administration, the Reagan team developed the strategies that brought us to the brink of the Cold War's peaceful conclusion, and remade the world"--